Strategies for Promoting Inclusive Education in the General Education and Training Phase in Rural Schools, the Case of a Grade 9 Economic Management Sciences Classroom in Limpopo Province – South Africa - Khutso Pitso Mankgele (E-Journal of Humanities, Arts and Social Sciences)
This study explored strategies for promoting inclusive education in Grade 9 economic management sciences (EMS) classrooms in rural schools within Limpopo Province, South Africa, using a qualitative, case study approach. Data from semi-structured interviews and focus group discussions with 20 participants, including EMS teachers, departmental heads, and principals, revealed five key themes: Differentiated instruction and teaching adaptation, teacher training and professional development, collaboration and support structures, challenges in resource availability, and leadership and administrative support for inclusion. The study highlights that despite the significant challenges rural schools face, there are actionable strategies, such as enhanced professional development, differentiated instruction, and increased collaboration, that can promote inclusivity in EMS classrooms. These findings provide valuable insights for educators and policymakers aiming to advance inclusive education in economically disadvantaged areas.